PENGELOLAAN PROGRAM TUJUH BERKAH PAJAK DAERAH DALAM PENINGKATAN KEPATUHAN WAJIB PAJAK OLEH UPT SAMSAT SIMPANG TIGA PROVINSI RIAU KOTA PEKANBARU TAHUN 2023 - Utama, Fajar Fadilla; ', Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This study aims to describe the Management of the Seven Regional Tax Blessings Program in Increasing Taxpayer Compliance by UPT Samsat Simpang Tiga Riau Province Pekanbaru City in 2023, this study uses George Terry's theory. This study uses a qualitative method with a descriptive research type, this study was conducted in Pekanbaru City with the main location being UPT Samsat Simpang Tiga Riau Province. The types of data used in this study are primary data and secondary data, the data sources used are from UPT Samsat Simpang Tiga Riau Province with 4 informants. The data collection technique was carried out by interview, then by documentation. The data analysis technique used in this study was by collecting data first, after collecting the data obtained, the researcher analyzed the data, then described the data and finally drew conclusions. The results obtained in this study contained 4 indicators carried out, namely Planning, Organizing, Actuating, and Controlling. The findings in this study are that the management of the 7 Regional Tax Blessings Program carried out by the UPT Samsat Simpang Tiga Riau Province was carried out smoothly, and this activity provided satisfaction and positive benefits to the community. Keywords: Planning, organizing, mobilizing, supervising, programming